Analysis of Promotion, Price Perception, and Product Quality on Yamaha Motorcycle Purchase Decisions in Bintaro, South Tangerang - Azwar, Rully Choiril; Nurmahdi, Adi (Dinasti Publisher, 2025)
The increasing public demand for motorcycles has made the level of competition in the automotive industry, especially motorcycles, increasingly tight. This can be seen from the many motorcycle brands that have emerged to meet the needs of consumers. This study aims to determine